An Analysis of Women's Language Features used by the Three Indonesian Female Travel Bloggers - Sherin Putri Indanna; Arasuli Arasuli; Indah Damayanti (Journal of English Education and Teaching, 2022)
This research focuses on women’s language features used by the three Indonesian female travel bloggers on blogspot.com and wordpress.com. It was aimed to investigate types of women’s language features used by the three Indonesian female travel bloggers and the most dominant types of women’s language features used by the three Indonesian female travel bloggers. This research was carried out using descriptive qualitative research. The data came from the script of 15 blog posts written by the three Indonesian female travel bloggers. The findings revealed that the three Indonesian female travel bloggers utilized nine types of women’s language features, they are lexical hedges or fillers, tag question, rising intonation on declaratives, empty adjectives, intensifiers, hypercorrect grammar, super polite forms, avoidance of strong swear words, and emphatic stress. The scripts of the three Indonesian female travel bloggers contain a total of 628 language features. During the analysis of the data, it revealed that the researchers were unable to discover precise colour terms because it was unrelated to the 15 blog posts. There was no correlation among the theme on 15 blog posts and the ability to use precise colour terms back then. The three Indonesian female travel bloggers dominantly employed hypercorrect grammar to prove that they concerned about their grammar.